Lint‐O cooperates with L(3)mbt in target gene suppression to maintain homeostasis in fly ovary and brain. (22nd August 2022) - Yamamoto‐Matsuda, Hitomi; Miyoshi, Keita; Moritoh, Mai; Yoshitane, Hikari; Fukada, Yoshitaka; Saito, Kuniaki; Yamanaka, Soichiro; Siomi, Mikiko C
Abstract: Loss‐of‐function mutations in Drosophila lethal(3)malignant brain tumor [l(3)mbt] cause ectopic expression of germline genes and brain tumors. Loss of L(3)mbt function in ovarian somatic cells (OSCs) aberrantly activates germ‐specific piRNA amplification and leads to infertility. However, the underlying mechanism remains unclear. Here, ChIP‐seq for L(3)mbt in cultured OSCs and RNA‐seq before and after L(3)mbt depletion shows that L(3)mbt genomic binding is not necessarily linked to gene regulation and that L(3)mbt controls piRNA pathway genes in multiple ways. Lack of known L(3)mbt co‐repressors, such as Lint‐1, has little effect on the levels of piRNA amplifiers. Identification of L(3)mbt interactors in OSCs and subsequent analysis reveals CG2662 as a novel co‐regulator of L(3)mbt, termed "L(3)mbt interactor in OSCs" (Lint‐O). Most of the L(3)mbt‐bound piRNA amplifier genes are also bound by Lint‐O in a similar fashion. Loss of Lint‐O impacts the levels of piRNA amplifiers, similar to the lack of L(3)mbt. The lint‐O ‐deficient flies exhibit female sterility and tumorous brains. Thus, L(3)mbt and its novel co‐suppressor Lint‐O cooperate in suppressing target genes to maintain homeostasis in the ovary and brain. Synopsis: Lint‐O, a novel L(3)mbt interactor, cooperates with L(3)mbt to suppress piRNA amplification genes and other gene targets to maintain homeostasis in Drosophila ovary and brain. Lint‐O (CG2662) is identified as a novel co‐regulator of L(3)mbt L(3)mbt/Lint‐O control piRNA amplification genes in multiple ways independent of known L(3)mbt co‐factors such as Lint‐1 lint‐O‐deficient flies exhibit female sterility and tumorous brains similar to l(3)mbt‐deficient flies Abstract : Lint‐O, a novel L(3)mbt interactor, cooperates with L(3)mbt to suppress piRNA amplification genes and other gene targets to maintain homeostasis in Drosophila ovary and brain.